2021
DOI: 10.2147/ndt.s334229
|View full text |Cite
|
Sign up to set email alerts
|

Can Goal-Based Health Management Improve the Health Knowledge, Health Belief and Health Behavior in People at High Risk of Stroke? A Non-Randomized Controlled Trial

Abstract: Purpose: To examine the effectiveness of goal-based health management on health knowledge, health belief and health behavior in people at high risk of stroke. Patients and Methods: This is a two-armed and non-randomized controlled trial from May 31, 2020 to December 31, 2020. Participants were arranged to receive regular health care (n=126) or goal-based health management (n=126). The generalized estimation equation was used to analyze the changes in the participants' health knowledge, health belief and health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…Health belief is the driving force for healthy behavior change and the most direct influencing factor for health behavior improvement [ 34 ]. The intervention group's health management motivation was continuously generated and strengthened, and their health beliefs were greatly improved, which was consistent with the result of other researchers [ 35 , 36 ]. Compared to the results of the Meng Yao Wang's study [ 37 ], health behaviors of high-risk for stroke groups have been greatly improved after the intervention in this study.…”
Section: Discussionsupporting
confidence: 88%
“…Health belief is the driving force for healthy behavior change and the most direct influencing factor for health behavior improvement [ 34 ]. The intervention group's health management motivation was continuously generated and strengthened, and their health beliefs were greatly improved, which was consistent with the result of other researchers [ 35 , 36 ]. Compared to the results of the Meng Yao Wang's study [ 37 ], health behaviors of high-risk for stroke groups have been greatly improved after the intervention in this study.…”
Section: Discussionsupporting
confidence: 88%
“…This underscores the importance of researchers considering the economic circumstances of patients. Tailored intervention strategies should be developed to facilitate the adoption of health behaviour among patients, taking into account these economic factors (He et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Early studies highlighted medical staff in the health knowledge transmission. For example, medical professionals could effectively improve the health knowledge of people at high risk of stroke [ 44 ]. In addition, multiple studies indicated that health information could be disseminated by WeChat [ 45 , 46 ], internet/social media [ 47 , 48 ], visual messages [ 49 ], text books [ 50 ], blogs [ 51 ], social media [ 52 ], iPad-based app [ 53 ], short-video app TikTok [ 54 , 55 ], Sina Weibo [ 56 ], booklet [ 57 ], mass media [ 58 ], and web-based educational film [ 59 ].…”
Section: Literature Reviewmentioning
confidence: 99%